Pengaruh kualitas pelayanan, harga, dan lokasi terhadap kepuasan pelanggan PT.Dwi Karya Sartika - Krisna Marpaung, Fenny; N. Hutagalung, Irma; Mariana Tinambunan, Maria; Jeremi Siahaan, Nico; H. Siregar, Lamhoras (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
The purpose of the implementation of this research is to prove and determine the magnitude of the influence of the independent variable of service quality, the independent variable of price, and the independent variable of location on the dependent variable of customer satisfaction at PT.Dwi Karya Sartika Medan. The sampling technique used was random sampling, thus the sample used was to carry out regression testing on 84 research respondents and 30 study respondents to carry out the reliability and validity test. Hypothesis testing is to use multiple linear regression analysis. The results of the research implementation of the independent variable of service quality, the independent variable of price, and the independent variable of location contributed partially to the dependent variable of customer satisfaction PT.Dwi Karya Sartika. The result of the test of the coefficient of determination is 0.758, which means that the resulting or predicted influence of the free variable of service quality (X1), price free variable (X2), and location independent variable (X3) on the dependent variable of customer satisfaction (Y) is 75.8%, while the remaining 24.2% is predicted or influenced by independent variables which are not included in the implementation of this research. Â